Microstructure, material flow and tensile properties of A356 alloy thixoformed parts - Emerson Reginaldo de Freitas; Elcio Geraldo Ferracini Júnior; Vinicius Perezin Piffer; Maurizio Ferrante (Materials Research, 2004)
The present work examines microstructure, tensile properties and quality (porosity level) of two thixoformed products, namely an assembly of three cylindrical rods from which tensile samples were machined out, and a cup-shaped part. The material is an A356 aluminium alloy and the microstructural conditioning was carried out by the deformation - recrystallization technique. Additionally, the microstructures of an A356 ingot produced by the magnetic stirring process was also investigated. Results showed that solid fraction and soaking time in the semi-solid state determine the thixoforming forces, that very low porosity levels can be achieved and minimized by the maintenance of high pressures during solidification, and that the material flow during injection in the mould is relatively homogeneous, except for the material conditioned by magnetic stirring. Physical simulation experiments of the thixoforming process (rods) showed a strong correlation between liquid segregation and porosity level. Finally, the tensile properties were shown to be much higher that those of permanent cast samples.